As marcas de heterogeneidade enunciativa como estratégias argumentativas - Pinheiro, Carlos Eduardo Silva (2022)
The Text Linguistic, especially the one practiced in Brazil by the research group Protexto (CNPq), from the Federal University of Ceará, and by the Grupo de Estudos em Linguística Textual (Gelt/CNPq), from the University for International Integration of the Afro-Brazilian Lusophony, has assumed the theoretical assumptions that Enunciative Heterogeneities and Argumentation are constitutive conditions of texts. Therefore, these groups have sought to investigate the strategies mobilized by speakers in texts of different discursive genres and, to this end, claim an interdisciplinary dialogue between the fundamental assumptions of Text Linguistic, the theoretical apparatus of the Theory of Enunciation, by Jacqueline Authier- Revuz (1990, 1998, 1999, 2004, 2008, 2015, 2020) and the Theory of Argumentation in Discourses (TAD) by Ruth Amossy (2017, 2018, 2019). Following these assumptions and anticipating the expansion of the discussion around them, the present dissertation aimed to analyze the argumentative strategies played by the textual marks of Enunciative Heterogeneity in texts published in the digital social network Twitter. This study is justified by the alignment with the interest of LT in investigating how speakers construct meaning in and through texts when they manage argumentatively the voices that cross their utterance. Moreover, we intended to advance in the characterization of Enunciative Heterogeneities considering them not from a purely enunciative point of view, but textual and argumentative. Therefore, we follow Cavalcante et al. (2020a) in thinking about the modes of instantiation of heterogeneities in texts not as "discursive forms", as Authier-Revuz treats, but as "textual marks" in the argumentative texture of texts. Our interest in analyzing texts published on Twitter was justified by the linguistic, interactional and technological particularities that this digital media makes available for the construction of the meanings of the texts that circulate on it. Therefore, the study carried out on the use of Enunciative Heterogeneity marks as strategies mobilized for the construction of argumentation in texts is relevant, timely and necessary, since it allowed us to understand not only the way in which speakers represent themselves and others in their discourses, but, above all, how this representation constitutes a complex argumentative process used for persuasion.